2008
DOI: 10.1111/j.1574-6968.2008.01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal performance using anaerobic ammonium oxidation at low temperatures

Abstract: An anaerobic ammonium oxidation (anammox) process for ammonia-rich wastewater treatment has not been reported at temperatures below 15 degrees C. This study used a gel carrier with entrapped anammox bacteria to obtain a stable nitrogen removal performance at low temperatures. In a continuous feeding test, a high nitrogen conversion rate (6.2 kg N m(-3) day(-1)) was confirmed at 32 degrees C. Nitrogen removal activity decreased gradually with decreasing operation temperature; however, it still occurred at 6 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
52
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(60 citation statements)
references
References 21 publications
7
52
1
Order By: Relevance
“…By far no pure strains of AnAOB have ever been obtained (Dapena-Mora et al 2004). Probably because of their slow growth rate, anammox bacteria are reported to be vulnerable to some external conditions such as low temperature, high dissolved oxygen (DO), and some inhibitors (Dosta et al 2008;Hendrickx et al 2012;Isaka et al 2008;Zhang et al 2010a). Even though facing quite a few difficulties in full-scale applications such as long-time start-up (van der Star et al 2007) and instability, anammox is still an innovative technological advancement in depleting ammonia from wastewater.…”
Section: Introductionmentioning
confidence: 98%
“…By far no pure strains of AnAOB have ever been obtained (Dapena-Mora et al 2004). Probably because of their slow growth rate, anammox bacteria are reported to be vulnerable to some external conditions such as low temperature, high dissolved oxygen (DO), and some inhibitors (Dosta et al 2008;Hendrickx et al 2012;Isaka et al 2008;Zhang et al 2010a). Even though facing quite a few difficulties in full-scale applications such as long-time start-up (van der Star et al 2007) and instability, anammox is still an innovative technological advancement in depleting ammonia from wastewater.…”
Section: Introductionmentioning
confidence: 98%
“…This may lead to lower specific activities and growth rates for both anammox bacteria and AOB. Indeed, it was reported that the activities of anammox bacteria and AOB both decreased at 15 to 20°C (13,14) and that partial nitrification was difficult to achieve in winter because of the varying temperature of municipal wastewater (15). Nevertheless, several studies showed that nitrogen removal at a lower temperature by an anammox process can work (14,16,17); still, in none of these studies was it possible to maintain a stable anammox-AOB culture (nitritation-anammox) at temperatures lower than 20°C.…”
mentioning
confidence: 99%
“…Indeed, it was reported that the activities of anammox bacteria and AOB both decreased at 15 to 20°C (13, 14) and that partial nitrification was difficult to achieve in winter because of the varying temperature of municipal wastewater (15). Nevertheless, several studies showed that nitrogen removal at a lower temperature by an anammox process can work (14,16,17); still, in none of these studies was it possible to maintain a stable anammox-AOB culture (nitritation-anammox) at temperatures lower than 20°C. On the other hand, in natural ecosystems, such as Northern European soils and marine sediments, anammox bacteria thrive under much colder temperatures and very low ammonium concentrations (M range) (18,19).…”
mentioning
confidence: 99%
“…D1 [9]. For nitrate reduction and the anammox reaction, the apparent activation energy values are 52.1 and 94 kJ/mol, respectively [11,12]. These results indicated that 1,4-dioxane removal by 1,4-dioxane-degrading bacterium Pseudonocardia sp.…”
Section: Evaluation Of Temperature Dependency Of 14-dioxane Removal mentioning
confidence: 51%